Розвиток інституту глави держави в конституційній теорії то практиці України періоду Національного відродження 1917 - 1921 р. р. - Головатенко, В. І.; Головатенко, В. И.; Golovatenko, V. (My University, 2011)
The subject of this research is an analysis of the evolution of the head of state institution in Ukrainian constitutionalism during 1917 – 1921. The author examines key features of the Head of Ukrainian State status in its development aspect during the period of Central Rada, Hetmanate and Directorate of Ukrainian People's Republic. Some drafts of Ukrainian People's Republic Constitution concerning head of state status are reviewed.
Головатенко В. І. Розвиток інституту глави держави в конституційній теорії то практиці України періоду Національного відродження 1917 - 1921 р. р. / В. І. Головатенко // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 42. – С.312 - 324.
Keywords: інститут глави держави; період Національного відродження; конституційна теорія; конституційна практика; український конституціоналізм; институт главы государства; период Национального возрождения; конституционная теория; конституционная практика; украинский конституционализм; Institute president; the period of the National Revival; constitutional theory; constitutional practice; Ukrainian constitutionalism